Fabrication and Electrochemical Performance of Al-Doped ZnO Nanosheets on Graphene-Based Flexible Substrates - Yu, Qi; Rong, Ping; Ren, Shuai; Jiang, Liyun; Li, Yapeng (Frontiers in Materials, 2019)
In this work, Al-doped ZnO nanosheets (NSs) were successfully synthesized on graphene-coated polyethylene terephthalate (GPET) flexible substrate by hydrothermal method. Studies have indicated that with the addition of Al3+, the nanostructure of ZnO gradually grows from nanorods (NRs) to NSs, and the (100), (002) and (101) diffraction peak strength of ZnO that grow perpendicular to the substrate along the c-axis weakened. The mechanism of hydrothermal growth of Al-doped ZnO/GPET was also studied. The electrochemical properties of the samples were investigated by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS), and it is concluded that Al-doped ZnO NSs grown on GPET substrates has better capacitance performance than undoped ZnO NRs.